The Analisis korelasi struktur komunitas Gastropoda terhadap parameter lingkungan di Pulau Samai Fakfak menggunakan Principal Component Analysis - Bakri, Iskandar; Binur, Robi; Sinuraya, Sabarita; Mogea, Rina (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT:The coastal ecosystem of Samai Island is a complex interaction between various organisms, including gastropods, and their environment. Gastropods are members of the mollusk phylum, which are invertebrates. This study aims to analyze the correlation between the structure of the gastropod community and physicochemical parameters. The research was conducted on the coast of Samai Island, Fakfak Regency, West Papua Province. Using the transect line method at four sampling stations. The results, showed that the highest gastropod density was found at Station IV (80.2 ind/m2), while the lowest was recorded at Station I (21.8 ind/m2). The gastropod diversity index ranged from 2.36 to 3.14, indicating a medium category at Stations II, III, and IV, and a high category at Station I. The evenness index was high at all stations, with values ranging from 0.61 to 0.87, and there was no dominant species at any station. The physico-chemical parameters of the water at the research location include water temperature ranging from 29.5°C to 30.4°C, salinity between 33.19‰ and 33.94‰, dissolved oxygen (DO) between 5.35 mg/L and 5.74 mg/L, and water pH ranging from 8.41 to 8.65. These parameters influence the structure of the gastropod community along the coast of Samai Island, Fakfak.